PERANCANGAN SISTEM MONITORING PERKEMBANGAN BALITA MENGGUNAKAN MIKROKONTROLER ATMEGA328P TERINTEGRASI DENGAN DATABASE MYSQL DI POSYANDU PIAN RAYA KABUPATEN MUSIRAWAS - Rudi Kurniawan; Lukman Sunardi (LPPM UNIVERSITAS BINA INSAN, 2018)
Toddler development stage is an important thing to always follow-up. A child is not the same as a miniature adult. Small children are still experiencing a process of growth and development. These two processes are important for the child's future in terms of physical and brain development. Delays or abnormalities at the stage of toddler development can have a negative impact on the toddler. This is the reason why knowing the stage of toddler development becomes a very important thing. Monitoring toddler development can be more practical by utilizing a combination of technology between microcontroller control and database usage as a result of monitoring. Monitoring conducted on toddlers can include monitoring the development of body weight, monitoring body temperature, and monitoring the toddler's heart rate. This microcontroller can process data generated by load cell, temperature sensor and heartbeat sensors to be processed and displayed in real time using the web with a MySQL database. Users who have logged in can access data on the development of body weight, body temperature, and heart rate of toddlers with good and organized records wherever and whenever. So that toddler development can be known easily. Designing a monitoring system for toddler development using a microcontroller that is integrated with the MySQL database at the Posyandu Pian Raya Kabupatem Musi Rawas can be a good solution so that toddler development data can be controlled and accessed anytime.